Land Transportation in Jenin Governorate “A Geographical Study” - Mohammad Yousef Nemer Khateeb (My University, 2011)
This study addressed the issue of land transport as one of the subjects of Transportation Geography considered as one of the branches of Economic Geography. The study focused on Jenin Governorate, an area that was defined according to the Palestinian National Authority’s division after 1993 as being part of the West Bank of River Jordan. The study aimed to identify the current situation of transportation in Jenin Governorate in terms of the existent roads, traffic volume and the factors affecting it, in addition to the main problems that the transportation sector faces in this area. To achieve these goals, the researcher divided the study into six main chapters. Chapter one included the problem of the study, its importance, objectives and hypotheses, in addition to the methodology and previous studies. Chapter two included a study of the general characteristics of the road network in the Governorate which covered a number of subjects such as the classification of roads, their characteristics, length and the degree of slope each road has. In the third chapter, the researcher discussed the geographical factors affecting the road network and traffic in the Governorate; those included the natural factors in the area under study such as the geographical location, topography, geological structure, soil and climate characteristics of the area. Other factors included the human factors such as population, urbanism and economic activity, in addition to political developments especially the impact of the Separation Wall. In the fourth chapter, the researcher presented a study of the quantitative analysis of the main and secondary road network; the analysis included urban nodes, network density, detour index, connectivity index and the degree of centrality, in addition to traffic intensity on some roads. The fifth chapter included the different means of transportation in the Governorate and the problems that result from them, whereas in the sixth and final chapter the researcher included the main results and recommendations of the study. Among the results that the study has reached was the fact that the value of the detour index increased because of the topography of the area under study. Also, the study has shown that the road between Jenin and Nablus had the greatest traffic intensity in both directions (that is from Jenin to Nablus and vice versa). Moreover, the study revealed the extent to which the Separation Wall has affected the roads’ directions and traffic in the area. In addition to the results, the researcher presented a number of recommendations. First, he pointed out the importance of encouraging people to use public transport in order to reduce the impacts on the environment and alleviate traffic jam in the center of the Governorate especially during rush hour time. The researcher also highlighted the necessity to establish special institutions that are specialized in dealing with roads and road-related issues such as roads expansion and the construction of bridges and tunnels to reduce traffic jam especially at crossroads and intersections within the city. He also recommended increasing the green area around roads’ sides and in places that are subject to frequent traffic jams. Furthermore, he recommended the building of vertical parking lots for vehicles instead of the common horizontal ones in order to save space and avoid the elimination of more agricultural lands in the city.

تناولت هذه الدراسة النقل البري كموضوع في جغرافية النقل والمواصلات التي تعد إحدى فروع الجغرافيا الاقتصادية، حيث ركزت تلك الدراسة على محافظة جنين التي حددت وفق تقسيم السلطة الوطنية الفلسطينية بعد عام 1993م، والتي تعتبر جزءا من الضفة الغربية لنهر الأردن. هدفت هذه الدراسة إلى التعرف على الوضع الحالي لحركة النقل بالمحافظة من حيث الطرق وحجم و الحركة والعوامل المؤثرة فيها، إضافة إلى التعرف على أهم المشكلات التي تواجه النقل . ولتحقيق هذه الأهداف قسمت الدراسة إلى ستة فصول رئيسية حيث احتوى الفصل الأول على مشكلة الدراسة وأهميتها وأهدافها وفرضياتها، إضافة إلى منهج الدراسة والدراسات السابقة، أما الفصل الثاني فقد احتوى على دراسة الخصائص العامة لشبكة الطرق في المحافظة واشتمل على تصنيف الطرق وخصائصها وامتدادها وأطوالها ودرجة انحدارها، أما الفصل الثالث فقد تم فيه دراسة العوامل الجغرافية المؤثرة في شبكة الطرق وحركة النقل والتي تتمثل بالعوامل الطبيعية لمنطقة الدراسة كالموقع الجغرافي وطبيعة السطح والبناء الجيولوجي والتربة والخصائص المناخية، إضافة إلى تأثير العوامل البشرية المتمثلة بالسكان والعمران والنشاط الاقتصادي، وكذلك التطورات السياسية ، وخاصة اثر الجدار العازل، أما الفصل الرابع فقد اشتمل على دراسة التحليل الكمي لشبكة الطرق الرئيسة والثانوية واشتمل على العقد الحضرية وكثافة الشبكة ومؤشر الانعطاف، ومؤشر الترابط و درجة المركزية، إضافة إلى غزارة النقل على بعض الطرق . الفصل الخامس احتوى على وسائط النقل بالمحافظة والمشاكل الناتجة عنها، أما الفصل السادس فقد تضمن النتائج والتوصيات، والتي كان من أبرزها ارتفاع قيمة مؤشر الانعطاف، بسبب طبيعة الطبوغرافية لمنطقة الدراسة، كما أظهرت الدراسة أن طريق جنين _ نابلس استحوذ على المرتبة الأولى في غزارة النقل في كلا الاتجاهين، كما بينت الدراسة مدى تأثير الجدار العازل على اتجاهات الطرق وحركة النقل . ومن أهم التوصيات التي أشار إليها الباحث ضرورة تشجيع الناس على استخدام وسائط النقل العام من اجل تقليل الآثار البيئية، وكذلك التخفيف من أزمة المرور على مركز المحافظة وبخاصة في فترات الذروة النقلية. أشار الباحث إلى ضرورة إنشاء مؤسسات خاصة من اجل العناية بالطرق، إضافة إلى توسيع الطرق واستخدام مستويات مثل الجسور والأنفاق للتخفيف من الأزمات المرورية، وخاصة عند تقاطعات الطرق الرئيسة داخل مدينة جنين، كما أوصى الباحث بزيادة المساحة الخضراء حول جوانب الطرق وأماكن الاختناقات المرورية، وأوصى كذلك بالتوسع العمودي في المواقف بدلا من الانتشار الأفقي الذي يقضي على المزيد من أراضي المحافظة الزراعية.
النقل البري في محافظة جنين "دراسة جغرافية"